Vessel Visualization using Curvicircular Feature Aggregation. (1st July 2013) - Mistelbauer, G.; Morar, A.; Varchola, A.; Schernthaner, R.; Baclija, I.; Köchl, A.; Kanitsar, A.; Bruckner, S.; Gröller, E.
Abstract: Radiological investigations are common medical practice for the diagnosis of peripheral vascular diseases. Existing visualization methods such as Curved Planar Reformation (CPR) depict calcifications on vessel walls to determine if blood is still able to flow. While it is possible with conventional CPR methods to examine the whole vessel lumen by rotating around the centerline of a vessel, we propose Curvicircular Feature Aggregation (CFA), which aggregates these rotated images into a single view. By eliminating the need for rotation, vessels can be investigated by inspecting only one image. This method can be used as a guidance and visual analysis tool for treatment planning. We present applications of this technique in the medical domain and give feedback from radiologists.